1997
DOI: 10.1007/s004390050548
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome polymorphisms in Native American and Siberian populations: identification of Native American Y chromosome haplotypes

Abstract: We have initiated a study of ancient male migrations from Siberia to the Americas using Y chromosome polymorphisms. The first polymorphism examined, a C→T transition at nucleotide position 181 of the DYS199 locus, was previously reported only in Native American populations. To investigate the origin of this DYS199 polymorphism, we screened Y chromosomes from a number of Siberian, Asian, and Native American populations for this and other markers. This survey detected the T allele in all five Native American pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 22 publications
7
65
0
2
Order By: Relevance
“…Earlier, haplogroup Q1a3a has been discovered at a low frequency in Siberian Eskimos, Chukchi and Evens. 43,44 Karafet et al 43 have hypothesized that this haplogroup may have originated in the New World/eastern Beringia and that its infrequent presence in Northeast Siberian populations can be explained by back-migration from Alaska to Siberia. A search of Q1a3a-M3 STRhaplotypes revealed in Evens in the YHRD 3.0 database (http:// www.yhrd.org; release 36 built on 15 April 2011; 91 493 haplotypes within 686 world populations) has shown that matching haplotypes (for loci DYS19, DYS385a, DYS385b, DYS389I, DYS389II, DYS390, DYS391, DYS392 and DYS393) are rarely present in modern Native American populations.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, haplogroup Q1a3a has been discovered at a low frequency in Siberian Eskimos, Chukchi and Evens. 43,44 Karafet et al 43 have hypothesized that this haplogroup may have originated in the New World/eastern Beringia and that its infrequent presence in Northeast Siberian populations can be explained by back-migration from Alaska to Siberia. A search of Q1a3a-M3 STRhaplotypes revealed in Evens in the YHRD 3.0 database (http:// www.yhrd.org; release 36 built on 15 April 2011; 91 493 haplotypes within 686 world populations) has shown that matching haplotypes (for loci DYS19, DYS385a, DYS385b, DYS389I, DYS389II, DYS390, DYS391, DYS392 and DYS393) are rarely present in modern Native American populations.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining two markers, the YAP marker, common in populations of African ancestry, and the M3 SNP, characteristic of Native Americans, were genotyped by PCR and PCR-restriction fragment length polymorphisms, respectively, as described earlier. 13,14 The definition of the different haplogroups was made according to the YChromosome Consortium recommendations. 15 Native American, European and African paternal contributions were determined directly from haplogroup frequencies, considering worldwide phylogeographic information.…”
Section: Marker Selection and Genotypingmentioning
confidence: 99%
“…Although genetic approaches to the population history of Native Americans have mostly used either autosomal or mtDNA markers, a number of recent analyses have begun to exploit Y chromosome-specific variation (6)(7)(8)(9)(10)(11)(12). These studies have shown a consistent pattern of scarce haplotypic diversity in Native American populations.…”
mentioning
confidence: 99%
“…Of particular interest, because it is most likely a single event polymorphism, the DYS199 T allele has been detected only in Chuckchan populations of extreme northeastern Siberia (11,12). The presence of the T allele in these populations could imply that they inherited it from an ancestral population shared with Native Americans.…”
mentioning
confidence: 99%